Sosialisasi Pemanfaatan Tenaga Surya Sebagai Sumber Energi Listrik Di Desa Ciherang Pondok, Kabupaten Bogor - Arief Suardi Nur Chairat (Terang, 2020)
One of the obstacles faced in providing electricity in rural areas is renewable energy sources, especially solar energy, which potentially in all rural areas also require inexpensive costs plus a lack of knowledge about these technologies. With a variety of goodness that exists in solar energy, counseling or socialization must be given about its utilization. Ciherang Pondok Village is located on a plateau in the area of ​​Caringin District, Bogor Regency. The village is located at a strategic point, so it has enough light intensity to utilize solar power as a source of electrical energy. Extension activities are carried out by the lecture method to convey various general information about the use of solar power as a solution to the problem of electrical energy in the countryside. As a result, the knowledge of the local community increases and can apply directly independently how to use solar energy to be used as a source of electrical energy so that the availability of energy and people's access to energy are guaranteed at affordable prices in the long term while paying attention to environmental sustainability.